Desenvolvimento de um software para monitoramento online de pacientes vítimas de intoxicação exógena - Michel, Carlos Eduardo (2023)
Exogenous intoxication is a public health problem. It occurs when an individual comes into contact with some type of chemical substance, and it can be self-inflicted or accidental. In Brazil, 4.8 million cases occur per year, of which 192,000 lead to death. This study aimed to propose, test and validate a software, based on monitoring and exchanging information between the Poison Center (CI) and an Emergency Care Unit (UPA) located in the North of the State of Paraná. Seven steps were adopted: scope definition, planning, prototype creation, prototype validation, name creation, validation, and software implementation. The first stage dealt with defining the target audience (judges), and how the software would work. The second stage consisted of analyzing and creating the software content. The third stage consisted of creating a prototype in Portuguese. In the fourth stage, the prototype was tested for three months, by 17 judges with expertise in the subject (n=17). In the fifth stage, the software was named Monintox. The sixth stage was the validation of Monintox by the 17 judges, who evaluated technical and content aspects. The seventh and final stage included the results of the Monintox evaluation, which achieved a kappa of 0.843, being classified as the best achievable. The judges evaluated Monintox using the standardized usability testing questionnaire, SUMI (Software Usability Measurement Inventory), which was composed of fifty items that evaluate the user's view of the system. Validation of the software showed that both technical aspects and content of the software were adequate, but some changes had to be made based on the judges' suggestions. In the last stage, the effectiveness of the software as a support tool in communication between the CI and the UPA was proven. The software proved to be a great tool for monitoring patients victims of exogenous poisoning, as it makes all of their information available to the IC in real time. Also, by accompanying the patient from their entry into the emergency room until their discharge or transfer to the reference hospital, Monintox enabled the IC to provide appropriate management for each UPA patient, avoiding communication gaps and ensuring effective management. It is concluded that Monintox achieved its main objective, which was to avoid communication failures and minimize errors, proving to be capable of being used on a daily basis by both institutions covered by this study.